2008
DOI: 10.6026/97320630002235
|View full text |Cite
|
Sign up to set email alerts
|

RNAi and RNAa - The Yin and Yang of RNAome

Abstract: Abstract:RNA interference (RNAi) is a powerful technology with huge applications for functional genomics, target identification in drug discovery and elucidation of molecular signaling pathways. Current RNAi studies have demonstrated the clinical potential of small interfering RNAs (siRNAs) in metabolic diseases, cancer, AIDS, malaria, neurodegenerative disorders, dental diseases and other illnesses. Interestingly, recent studies have shown that the small RNA molecules, either indigenously produced as microRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 12 publications
0
22
0
2
Order By: Relevance
“…Thus, most of the previous functional studies are limited to the knockdown approach [22] . RNA activation-induced gene expression by targeting promoter sequence allowed us to physiologically and directly test the function of a given gene [2326] . In fact, lentiviral-based delivery of dsRNAs has been reported to activate VEGF expression by targeting promoter sequences in an ischemic mouse model [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, most of the previous functional studies are limited to the knockdown approach [22] . RNA activation-induced gene expression by targeting promoter sequence allowed us to physiologically and directly test the function of a given gene [2326] . In fact, lentiviral-based delivery of dsRNAs has been reported to activate VEGF expression by targeting promoter sequences in an ischemic mouse model [27] .…”
Section: Discussionmentioning
confidence: 99%
“…These include microRNAs (miRNAs), which inhibit protein translation by base-pairing with imperfect complementarity to target sequences within mRNA molecules; PIWIinteracting RNAs (piRNAs), which are involved in gene silencing by targeting transposons in animal germ cells; and small interfering RNAs (siRNAs) or RNA interference (RNAi), which target homologous mRNA sequences to degrade transcripts, leading to post-transcriptional gene silencing [ 3 -5 ]. A new addition can be made to this category, in the form of activating RNAs, the discovery of which was made serendipitously [ 6 ]. While attempting to silence E-cadherin gene transcription, using small double-stranded RNAs (dsRNAs) in human cells, Li et al [ 7 ] observed that several promoter-targeted dsRNA molecules were able to activate gene and protein expression.…”
Section: Introductionmentioning
confidence: 99%
“…This information also indicates a new obstacle for RNAi, in which siRNAs may undesirably stimulate the expression of off-target genes. Hence, it can be stated that both RNAa and RNAi constitutes the Yin and Yang of the RNAome in living organisms (Pushparaj et al, 2008a). RNAi AS NOVEL THERAPEUTICS -IS IT IMMINENT?…”
Section: Major Challenges Of Rnai Therapeuticsmentioning
confidence: 99%